NAFLD and thyroid function: pathophysiological and therapeutic considerations - Hatziagelaki, Erifili; Paschou, Stavroula A.; Schön, Martin; Psaltopoulou, Theodora; Roden, Michael (Trends in endocrinology and metabolism, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a worldwide rising challenge because of hepatic, but also extrahepatic, complications. Thyroid hormones are master regulators of energy and lipid homeostasis, and the presence of abnormal thyroid function in NAFLD suggests pathogenic relationships. Specifically, persons with hypothyroidism feature dyslipidemia and lower hepatic β-oxidation, which favors accumulation of triglycerides and lipotoxins, insulin resistance, and subsequently de novo lipogenesis. Recent studies indicate that liver-specific thyroid hormone receptor β agonists are effective for the treatment of NAFLD, likely due to improved lipid homeostasis and mitochondrial respiration, which, in turn, may contribute to a reduced risk of NAFLD progression. Taken together, the possible coexistence of thyroid disease and NAFLD calls for increased awareness and optimized strategies for mutual screening and management. Hypothyroidism is present in a significant proportion of people with nonalcoholic fatty liver disease (NAFLD) and may contribute to their higher all-cause as well as cardiovascular mortality. Accelerated hepatic de novo lipogenesis and adipose tissue-derived fatty acid flux to the liver with subsequent insulin resistance may contribute to this association.International guidelines recommend screening for liver disease in all adults with hypo- or hyperthyroidism and for thyroid disease in those with NAFLD.Novel selective thyroid hormone receptor β agonists have been developed to combat NAFLD, but possible extrahepatic effects need close monitoring.